2015
DOI: 10.1111/1471-0528.13569
|View full text |Cite
|
Sign up to set email alerts
|

Do labetalol and methyldopa have different effects on pregnancy outcome? Analysis of data from the Control of Hypertension In Pregnancy Study (CHIPS) trial

Abstract: Objective To compare pregnancy outcomes, accounting for allocated group, between methyldopa-treated and labetalol-treated women in the CHIPS Trial (ISRCTN 71416914) of 'less tight' versus 'tight' control of pregnancy hypertension.Design Secondary analysis of CHIPS Trial cohort.Setting International randomised controlled trial (94 sites, 15 countries).Population or sample Of 987 CHIPS recruits, 481/566 (85.0%) women treated with antihypertensive therapy at randomisation. Of 981 (99.4%) women followed to deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 25 publications
4
21
0
5
Order By: Relevance
“…Very preterm delivery at <34 weeks was more common among women who were in hospital at enrolment or had higher BP, and less common among women were enrolled at later gestational ages, had preexisting (vs. gestational hypertension) or were taking methyldopa as their antihypertensive agent at enrolment (as previously reported) (Figure e). No significant interactions were identified.…”
Section: Resultssupporting
confidence: 69%
“…Very preterm delivery at <34 weeks was more common among women who were in hospital at enrolment or had higher BP, and less common among women were enrolled at later gestational ages, had preexisting (vs. gestational hypertension) or were taking methyldopa as their antihypertensive agent at enrolment (as previously reported) (Figure e). No significant interactions were identified.…”
Section: Resultssupporting
confidence: 69%
“…Following adjusted analyses, methyldopa (vs. labetalol) at randomisation was associated with fewer babies with a birthweight <10th centile. Methyldopa (vs. labetalol) post randomisation was associated with fewer CHIPS primary outcomes, birthweight <10th centile, severe hypertension, pre-eclampsia and delivery before both 34 and 37 weeks [92].…”
Section: Medical Solutionsmentioning
confidence: 93%
“…Recent evidence (although not from a randomized head-tohead comparison) suggested that this agent may be associated with benefit in maternal and perinatal outcome compared with labetalol, and it should be considered for inclusion in a definitive trial. 25 In the nonpregnant population, there is evidence that some antihypertensive agents have additional therapeutic benefits beyond reduction in arterial BP, including anti-inflammatory and oxidative stress-lowering properties. 26 Given the role of inflammation and oxidative stress in the pathophysiology of preeclampsia, 27 future research should further explore the mechanistic actions of each drug to establish if other therapeutic benefits exist in pregnancy.…”
Section: Downloaded Frommentioning
confidence: 99%